(3LhGgQ GdcdGe TQM TQGFY GdESdGes - (3GdfLaj, eMeO GdfLaj, eMeO MSf Hf HGbQ, J (B1266(3g` (B1850(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdaUd GdYGTQ ef aUhd cJGH GdJLGQI aj GdSda hGdfXQ ajg jSJOYj ebGUO GdChd aj MbjbI GdSde HaJM GdSjf hGddGe GdPj gh eQGOa ddaX GdSdas
(3BNQgG (B:s
(3BNQgG(B: (3CeG GdKGfj agh hGVM GdaSGO hcja cGf aMed GdYHGQI Ydi Pdc eecf hEf cGf HYjkOG Hd QHeG fhbT ajeG SeYJg ef hLhg GdGTcGd hCfg jJYjf HGdUMI (B... (3Je GdeLdO GdKGdK ef GdYbhOs
(3GdfSNI ebGHdI Ydi eShOI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 214s
(3GdPQjYI, L (B5: 196s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis